2014
DOI: 10.1111/jcmm.12200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of type‐I Interferon receptor expression level on the response to type‐I Interferons in human pancreatic cancer cells

Abstract: Pancreatic cancer is a highly aggressive malignancy with limited treatment options. Type-I interferons (e.g. IFN-α/-β) have several anti-tumour activities. Over the past few years, clinical studies evaluating the effect of adjuvant IFN-α therapy in pancreatic cancer yielded equivocal results. Although IFN-α and-β act via the type-I IFN receptor, the role of the number of receptors present on tumour cells is still unknown. Therefore, this study associated, for the first time, in a large panel of pancreatic canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 46 publications
2
38
0
4
Order By: Relevance
“…Overall, modulation of TNFa activity and its cellular effects depends on many factors: levels of soluble mediators, absolute count of cells with receptors, the ratio of subsets in terms of cell percentage and receptor density, intracellular protein content of the target cell, and the ratio of Type I to Type II receptors per single cell, and regulation of these parameters is significantly changed in RA. An important mechanism by which its functions are regulated in normal cells and under pathological conditions is variation of the receptor expression density [36,40]. With allowance for the fact that signaling can only be induced above a threshold soluble cytokine level and membrane-bound receptors are as important in binding to the mediator, it is logical to suggest that signal transduction correspondingly requires a certain amount of receptors expressed on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, modulation of TNFa activity and its cellular effects depends on many factors: levels of soluble mediators, absolute count of cells with receptors, the ratio of subsets in terms of cell percentage and receptor density, intracellular protein content of the target cell, and the ratio of Type I to Type II receptors per single cell, and regulation of these parameters is significantly changed in RA. An important mechanism by which its functions are regulated in normal cells and under pathological conditions is variation of the receptor expression density [36,40]. With allowance for the fact that signaling can only be induced above a threshold soluble cytokine level and membrane-bound receptors are as important in binding to the mediator, it is logical to suggest that signal transduction correspondingly requires a certain amount of receptors expressed on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this, initiation of different pathways, which can eventually lead to a particular outcome in the cell, also depends on the factors recruited to the cytokine-receptor complex. Another important mechanism by which cytokine activities and the variability of their biological effects are regulated is the modulation of surface receptor density on the cell membrane [36,37] and the number of receptors which are equivalent participants of ligand-cell interactions regulating the type and extent of the immune response. Therefore, to study changes in the system of membrane-bound forms of receptors and the cytokine itself, it is essential to evaluate not only the number of cells expressing Type I and II receptors, but also the absolute number of receptors.…”
Section: Introductionmentioning
confidence: 99%
“…3b) showed that the HPDE6 cell supernatants, containing IFN-b but not infectious virus, were capable of inducing apoptosis in various PDA cell lines to different extents. Indeed, diverse degrees of sensitivity to exogenous IFN-b, depending on the PDA cell line, have been previously reported (Booy et al, 2014;Vitale et al, 2007). Consistently with previous findings, BxPC-3 and AspC-1 cell lines displayed the highest sensitivity to conditioned media that contained IFN, followed by CFPAC-1, the more resistant Mia Paca-2 and finally by the non-malignant ductal pancreatic HPDE6 cells.…”
Section: The Immunostimulatory Activity Of H7n3 Ns1-77 Virus In Infecmentioning
confidence: 99%
“…IFN-a and -b are multifunctional cytokines that have shown efficacy in the treatment in vitro and in vivo of several tumours types including PDAs (Booy et al, 2014;Lindner et al, 1997;Tomimaru et al, 2011;Vitale et al, 2006Vitale et al, , 2007.…”
Section: The Immunostimulatory Activity Of H7n3 Ns1-77 Virus In Infecmentioning
confidence: 99%
“…Receptors and mediators are equally involved in promoting biological effects in target cells and the regulation of these effects can be modulated via different mechanisms such as the expression density of receptors on the cell surface and the level of soluble receptors, which affect the type and intensity of responses [1, 2]. Recent studies demonstrated that the functional response of cells to a me­diator can be altered by modifying the expression of receptors or can be fundamentally different after a certain level of receptors is expressed [3].…”
Section: Introductionmentioning
confidence: 99%